100 chefs-d'œuvre du design : dans les collections du Centre Pompidou - Guichon, Françoise; Migayrou, Frédéric (Paris : Éditions du Centre Pompidou, 2011)
Wagner, Otto ; Behrens, Peter ; Atelier Gras ; Chareau, Pierre ; Schmidt, Joost ; Hartwig, Josef ; Breuer, Marcel ; Le Chevallier, Jacques ; Mallet-Stevens, Robert ; Liber, Henri ; Perriand, Charlotte ; Jourdain, Francis ; Gray, Eileen ; Le Corbusier ; Jeanneret, Pierre ; Pagano, Giuseppe ; Djo-Bourgeois ; Herbst, René ; Sognot, Louis ; Prouvé, Jean ; Guillot, Émile ; Lurçat, André ; Prouvé, Jean ; Aalto, Alvar ; Rietveld, Gerrit ; Beaudouin, Eugène ; Lods, Marcel ; Ponti, Gio ; Coulon, René ; Coray, Hans ; Mathsson, Bruno ; Saarinen, Eero ; Eames, Charles ; Eames, Ray ; Bic ; Mollino, Carlo ; Wegner, Hans J. ; Zanuso, Marco ; Bertoia, Harry ; Laverrière, Janette ; Kjærholm, Poul ; Mouille, Serge ; Guhl, Willy ; Sarfatti, Gino ; Noguchi, Isamu ; Borsani, Osvaldo ; Henningsen, Poul ; Abraham, Janine ; Rol, Dirk Jan ; Nelson, George ; Jacobsen, Arne ; Guariche, Pierre ; Castiglioni, Achille ; Castiglioni, Pier Giacomo ; Rams, Dieter ; Colombo, Joe ; Tallon, Roger ; Mourgue, Olivier ; Sapper, Richard ; Paulin, Pierre ; Aulenti, Gae ; Haus-Rucker-Co ; Held, Marc ; La Pietra, Ugo ; Archizoom Associati ; Sottsas, Ettore ; Superstudio ; Bellini, Mario ; Kuramata, Shiro ; Panton, Verner ; Widmer, Jean ; Niemeyer, Oscar ; Pesce, Gaetano ; Cadestin, Michel ; Mendini, Alessandro ; Cieslewicz, Roman ; Garouste, Élisabeth ; Bonetti, Mattia ; Szekely, Martin ; De Lucchi, Michele ; Starck, Philippe ; Colani, Luigi ; Branzi, Andrea ; Newson, Marc ; Van Severen, Maarten ; Bouroullec, Ronan ; Bouroullec, Erwan ; Yoshioka, Tokujin ; Jouin, Patrick ; Ishigami, Junya ; Demakersvan ; Arad, Ron ; Campbell, Louise ; Charpin, Pierre ; Laarman, Joris ; Szekely, Martin
boek